2017
DOI: 10.7454/jki.v20i2.365
|View full text |Cite
|
Sign up to set email alerts
|

Kejadian Excessive Daytime Sleepiness (Eds) Dan Kualitas Tidur Pada Mahasiswa Kesehatan

Abstract: AbstrakKejadian Excessive Daytime Sleepiness (EDS) merupakan gejala yang timbul dari kecenderungan untuk merasakan kantuk yang berlebihan pada periode terjaga. Penelitian ini bertujuan untuk mengidentifikasi hubungan antara kejadian EDS dengan kualitas tidur pada mahasiswa baru di rumpun ilmu kesehatan. Desain penelitian ini adalah dengan pendekatan potong lintang menggunakan sampel mahasiswa Rumpun Ilmu Kesehatan sebesar 107 responden yang dipilih dengan teknik proportional stratified random sampling. Kejadia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
1
4
1
7
Order By: Relevance
“…Acceptable internal consistency and test-retest reliability were previously established (Cronbach's α = 0.88, r = 0.82) (Johns, 1992). The validity test results firmly established the validity of all items in the Indonesian version of the ESS (r ≥ 0.4), and the reliability test results also confirmed that the ESS was reliable (Bambangsafira and Nuraini, 2017). In the present study, students with a total ESS score of > 10 were considered to have excessive daytime sleepiness.…”
Section: Epworth Sleepiness Scalesupporting
confidence: 53%
“…Acceptable internal consistency and test-retest reliability were previously established (Cronbach's α = 0.88, r = 0.82) (Johns, 1992). The validity test results firmly established the validity of all items in the Indonesian version of the ESS (r ≥ 0.4), and the reliability test results also confirmed that the ESS was reliable (Bambangsafira and Nuraini, 2017). In the present study, students with a total ESS score of > 10 were considered to have excessive daytime sleepiness.…”
Section: Epworth Sleepiness Scalesupporting
confidence: 53%
“…Based on the study results, the incidence of drowsiness during the day of the majority of respondents was in the normal category. According to Bambangsafira & Nuraini (2017), Excessive Daytime Sleepiness (EDS) is a symptom arising from the tendency to feel excessive sleepiness during the waking period, where EDS is also a neurological disorder that causes excessive daytime sleepiness. The EDS is caused due to several factors, including watching movies or videos, communicating via telephone, SMS, chatting, online on social media, receiving messages or calls before bed, and sending messages/ calls before going to bed either when the lights are on, or the lights are off (Wilson, Reid, Braun, Abbott, & Zee, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The dependent variable was the incidence of drowsiness measured by Epworth Sleepiness Scale (ESS). The ESS questionnaire validity test result in Bahasa Indonesia stated that all items were valid (r 4) and reliable (Bambangsafira & Nuraini, 2017). Students who have a total ESS score > 10 were considered to have excessive daytime sleepiness (Marta et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Rasa kantuk yang berlebihan akan mempengaruhi konsentrasi, fungsi ingatan (memori), pengontrolan emosi serta membuat individu menjadi mudah marah. Hal tersebut mengakibatkan terjadinya gangguan / perubahan pada mood serta penurunan kondisi kesehatan dan kemampuan belajar dan dapat menyebabkan kecelakaan dalam berkendara (Alzahrani et al, 2016;Bambangsafira & Nuraini, 2017). Hal ini didukung penelitian Gaultney (2010) yang dilakukan kepada mahasiswa yang mengalami EDS didapatkan hasil yaitu 21% mempunyai nilai akademik yang buruk, 16% menyatakan pernah tertidur saat berkendara, serta 2% mengalami kecelakaan bermotor (Taylor & Bramoweth, 2010).…”
Section: Pendahuluanunclassified